Sejarah Public Relations di Indonesia: dari 'Penipu' Menjadi Penasihat Tepercaya - Sumardiyantoro, Iven (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
In recent years, there has been an increased interest in the history of public relations, as well as a growing body of academic research into the study of public relations. Public relations initially became an agenda for the dissemination of deceptive information. Furthermore, developing into efforts to provide correct information. This study uses historical analysis to determine the development of public relations in Indonesia. Data was collected through literature and document reviews. This research found that the stages of developing public relations through a complicated and long process. Not only that, public relations develops with other multidisciplinary disciplines, including marketing. In Indonesia, the history of public relations practices has been going on for a long time, as long as Indonesia. However, formally, it started when Bakohumas was founded.